2019
DOI: 10.1111/adb.12870
|View full text |Cite
|
Sign up to set email alerts
|

Reduced responsiveness of the reward system is associated with tolerance to cannabis impairment in chronic users

Abstract: Cannabis is the most commonly used illicit drug in the world. However, because of a changing legal landscape and rising interest in therapeutic utility, there is an increasing trend in (long-term) use and possibly cannabis impairment. Importantly, a growing body of evidence suggests that regular cannabis users develop tolerance to the impairing, as well as the rewarding, effects of the drug. However, the neuroadaptations that may underlie cannabis tolerance remain unclear. Therefore, this double-blind, randomi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 59 publications
(134 reference statements)
4
43
0
Order By: Relevance
“…Most prominent were decrements in functional connectivity between the subcortical and the dorsal attention network, and between the limbic and cerebellar networks that suggest a reduction of top-down attention control 63 and motor coordination 64 during cannabis intoxication. These findings of reduced connectivity are largely in line with a series of studies that predominantly reported hypoconnectivity within brain circuits as a primary response during cannabis intoxication 10,11,27 . A parallel increment in functional connectivity however was apparent between the default mode network and the ventral attention network.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Most prominent were decrements in functional connectivity between the subcortical and the dorsal attention network, and between the limbic and cerebellar networks that suggest a reduction of top-down attention control 63 and motor coordination 64 during cannabis intoxication. These findings of reduced connectivity are largely in line with a series of studies that predominantly reported hypoconnectivity within brain circuits as a primary response during cannabis intoxication 10,11,27 . A parallel increment in functional connectivity however was apparent between the default mode network and the ventral attention network.…”
Section: Discussionsupporting
confidence: 86%
“…The current study was registered in the Netherlands trial register (NTR4897). A previous analysis of THC effects on seed-based functional connectivity within the mesocorticolimbic circuit employing the same data set has been published elsewhere 11 .…”
Section: Methodsmentioning
confidence: 99%
“…In regards to power analysis for imaging data, this is quite complex, with the most common approach in the neuroimaging community is to estimate the number of subjects from previous empirical experience in the field. Previous MRS and FC studies have employed 10-21 subjects for showing significant drug effects [63][64][65] . Based on these experiences, we expected that we would be able to demonstrate drug effects on MRS and FC in 30 participants in each drug condition.…”
Section: Sample Size Calculationmentioning
confidence: 99%
“…These data support a recent PET imaging study demonstrating that cannabis-dependent patients show a deficit in striatal DA release after the investigators controlled for several comorbidities that may have influenced previous imaging studies ( van de Giessen et al, 2017 ). In another noteworthy imaging study, Mason et al (2021) used resting-state functional magnetic resonance imaging (fMRI) to determine functional connectivity between the NAc and other brain regions of interest in occasional and chronic cannabis users. Both groups received placebo and 300-μg/kg THC on separate days.…”
Section: Introductionmentioning
confidence: 99%